Suppression of certain intestinal microbiota metabolites may lead to gestational diabetes in mice fed a high-fat diet - Xie, Ya-ping; Zhao, Hui-fen; Lin, Shu; Wang, Xian-long; Liu, Yi-fei; Xie, Bao-yuan (Frontiers in Microbiology, 2024)
Abstract Background: We aim to establish a gestational diabetes mellitus (GDM) mouse model with mice fed with a high-fat diet (HFD) in comparison with pregnant mice with normal blood glucose levels to investigate the role of intestinal microbiota in the development of HFD-induced GDM. Methods: We divided healthy 6-week-old female C57BL mice into an HFD-induced GDM group and a normal diet group. Their bacterial flora and metabolites in intestinal fecal exosomes were co-analysed using 16s multi-region sequencing and compared. Findings: Alpha (α) diversity was lower within the model group compared to the control group. Beta (β) diversity was significantly different between the two groups. The relative abundances of Lactobacillus, Actinomyces, Rothia, and Bacteroidetes were significantly different between the two groups. Fermentation and nitrate consumption were significantly higher in the GDM group. Multiple bacteria were associated with glycerophosphocholine, S-methyl-5′-thioadenosine, quinolinate, galactinol, deoxyadenosine, DL-arginine, and 2-oxoadenic acid. Interpretation: Imbalances in the production of Lactobacillus, Bacteroidetes, Actinomyces, and Rothia and their related metabolites may lead to metabolic disturbances in GDM. These indicators may be used to assess changes affecting the intestinal microbiota during pregnancy and thus help modulate diet and alter blood glucose.